Effects of phosphogypsum, superphosphate, and dicyandiamide on gaseous emission and compost quality during sewage sludge composting. (December 2018) - Yuan, Jing; Li, Yun; Chen, Shili; Li, Danyang; Tang, Huan; Chadwick, David; Li, Shuyan; Li, Wangwang; Li, Guoxue
Highlights: PPG decreased NH3 and CH4 but increased N2 O emissions during composting. SSP significantly reduced NH3, CH4, and N2 O emissions during composting. Additions of DCD markedly reduced N2 O emissions during composting. SSP and DCD reduced NH3, CH4 and N2 O by 12.3%, 81.0% and 88.2%, respectively. PPG and SSP increased struvite levels, raising compost quality. Abstract: This study investigated the effects of phosphogypsum, superphosphate, and dicyandiamide on gaseous emission and compost quality during sewage sludge composting. Results showed that phosphogypsum reduced ammonia (NH3 ) and methane (CH4 ) emissions but increased nitrous oxide (N2 O) emission. Superphosphate simultaneously reduced NH3, N2 O and CH4 emissions. Dicyandiamide markedly reduced N2 O emission during composting. Combination of phosphogypsum and dicyandiamide reduced CH4 and N2 O emissions by 75.6% and 86.4%, while NH3 emission was increased by 22.0%. Combination of superphosphate and dicyandiamide reduced NH3, CH4 and N2 O emissions by 12.3%, 81.0% and 88.2%, respectively. More importantly, with the addition of 10% initial raw materials, phosphogypsum and superphosphate conserved nitrogen and improved compost quality by introducing additional nutrients.